Positive regulation of TRAF6-dependent innate immune responses by protein phosphatase PP1-γ. - Amanda M Opaluch; Monika Schneider; Chih-yuan Chiang; Quy T Nguyen; Ana M Maestre; Lubbertus C F Mulder; Ismael Secundino; Paul D De Jesus; Renate König; Viviana Simon; Victor Nizet; Graham MacLeod; et al. (PLoS ONE)
Innate immune sensors such as Toll-like receptors (TLRs) differentially utilize adaptor proteins and additional molecular mediators to ensure robust and precise immune responses to pathogen challenge. Through a gain-of-function genetic screen, we identified the gamma catalytic subunit of protein phosphatase 1 (PP1-γ) as a positive regulator of MyD88-dependent proinflammatory innate immune activation. PP1-γ physically interacts with the E3 ubiquitin ligase TRAF6, and enhances the activity of TRAF6 towards itself and substrates such as IKKγ, whereas enzymatically inactive PP1-γ represses these events. Importantly, these activities were found to be critical for cellular innate responses to pathogen challenge and microbial clearance in both mouse macrophages and human monocyte lines. These data indicate that PP1-γ phosphatase activity regulates overall TRAF6 E3 ubiquitin ligase function and promotes NF-κB-mediated innate signaling responses.